2010
DOI: 10.3109/00016480903413657
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cholesteatoma growth and secretion of cytokines

Abstract: We found a radial outgrowth of keratinocyte epithelium from the circular biopsies. After 5 days of culture we found a significant growth of both cholesteatoma and skin-derived cells. Cholesteatoma samples showed higher growth rate as compared with skin control cultures from the same patient. Moreover, the cholesteatoma cells showed higher production of monocyte chemoattractant protein-1 (MCP-1) and interleukin (IL)-6 as compared with normal skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
1
4
0
1
Order By: Relevance
“…and Helgaland et al . 34 , 35 , who reported that in vitro growth of cholesteatoma cells is faster than that of cells derived from normal EAC skin, our results showed a lower proliferation of cholesteatoma cells than normal skin cells. This finding is in agreement with other studies where cholesteatoma-derived cells demonstrated lower colony-forming efficiency, fewer passages, and a shorter lifespan compared with normal skin–derived cells 35 37 .…”
Section: Discussionsupporting
confidence: 57%
“…and Helgaland et al . 34 , 35 , who reported that in vitro growth of cholesteatoma cells is faster than that of cells derived from normal EAC skin, our results showed a lower proliferation of cholesteatoma cells than normal skin cells. This finding is in agreement with other studies where cholesteatoma-derived cells demonstrated lower colony-forming efficiency, fewer passages, and a shorter lifespan compared with normal skin–derived cells 35 37 .…”
Section: Discussionsupporting
confidence: 57%
“…We previously discovered that the expression of IL‐6 and p‐STAT3 were significantly higher in cholesteatoma epithelium than in normal external auditory canal epithelium . Helgaland et al discovered an obviously elevated secretion of IL‐6 in cholesteatoma epithelial cells in vitro . In addition, Ho et al found that up‐regulation of STAT3 was presented in cholesteatoma tissues .…”
Section: Cell Proliferation Signal Pathwaysmentioning
confidence: 98%
“…4 Dalam hal ini osteoklas distimulasi sitokinsitokin tertentu seperti IL-6. 10,11,20 Kadar IL-6 pada kolesteatoma subjek penelitian Pada analisis sampel kolesteatoma didapatkan adanya IL-6. Literatur menyebutkan bahwa perimatriks maupun matriks kolesteatoma dapat menghasilkan IL-6.5,8 TNF-α, IL-1 dan IL-6 didapatkan pada kolesteatoma dalam konsentrasi tinggi.…”
Section: Distribusi Derajat Kerusakan Tulang Pendengaran Pada Subjek Penelitianunclassified